تأثير تقلبات سعر الصرف الاسمي على حجم التبادل التجاري في سورية خلال الفترة الزمنية (1990- 2010) - زنبوعه, محمود; حبيب, راقي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى دراسة تأثير تقلبات سعر الصرف الاسمي على التبادل التجاري في الجمهورية العربية السورية خلال الفترة الزمنية (1990- 2010) وتحديد اتجاه تلك الآثار وطبيعة تأثيرها عليه. ولتحقيق هدف الدراسة تم جمع بيانات حول سعر الصرف والتبادل التجاري في سورية خلال الفترة الزمنية (1990- 2010) وذلك بالاعتماد على المكتب المركزي للإحصاء والنشرات الربعية لمصرف سورية المركزي للسنوات المذكورة. وبعد ذلك قام الباحث بتحليل البيانات باستخدام برنامج (Eviews 8) الإحصائي في دراسة العلاقة بين سعر الصرف وحجم التبادل التجاري عن طريق تحليل استقرار السلاسل الزمنية واختبار التكامل المشترك ونموذج تصحيح الخطأ. وقد توصلت الدراسة للنتائج التالية:هناك علاقة عكسية بين التقلبات في سعر الصرف والتبادل التجاري في الأجل القصير خلال الفترة الزمنية (1990- 2000) وهذا يوافق فرضية التأثير السلبي لتقلبات سعر الصرف على التجارة، ولا توجد علاقة في المدى الطويل بين التقلبات في سعر الصرف الاسمي والتبادل التجاري.This research aims to study the effect of exchange rate fluctuations on trade in the Syrian Arab Republic during the time period (1990- 2010) and determine the direction of these effects and the nature of their impact on it. To achieve the objective of the study was to collect data on the exchange rate and trade in Syria during the time period (1990- 2010) relying on the Central Bureau of Statistics and quarterly releases to Central Bank of Syria for the aforesaid years. After that, the researcher analyzed the data using a program (Eviews 8 EMI) in the study of the relationship between the exchange rate and trade by the stability of time-series and test the joint integration and error correction model analysis. The study found the following results:There is an inverse relationship between the fluctuations in the exchange rate and trade in the short term during the time period (1990- 2010) and agrees that the negative effect of exchange rate fluctuations on trade hypothesis, and there is no relationship in the long term between the fluctuations in the nominal exchange rate and trade.